2016
DOI: 10.21037/atm.2016.03.10
|View full text |Cite
|
Sign up to set email alerts
|

What is new for the prevention of catheter-related bloodstream infections?

Abstract: After the publication in 2011 of latest guidelines of the Centers for Disease Control and Prevention (CDC) for the prevention of catheter-related bloodstream infections (CRBSI) some interesting findings have been published in that field. There has been published that skin disinfection with chlorhexidine alcohol reduced the risk of CRBSI compared to skin disinfection with povidone iodine alcohol, that the implementation of quality improvement interventions reduced the incidence of CRBSI, that the use of chlorhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…It further supports the recommendation that fistula and graft use should be promoted among dialysis patients [12,13]. For those patients unable or unwilling to use a fistula or graft, multiple studies have shown that chlorhexidine use at the catheter vascular access site reduces the incidence of BSIs [12,13,16]. Appropriate use of this antiseptic may also help reduce BSIs in catheterized patients.…”
Section: Discussionsupporting
confidence: 57%
“…It further supports the recommendation that fistula and graft use should be promoted among dialysis patients [12,13]. For those patients unable or unwilling to use a fistula or graft, multiple studies have shown that chlorhexidine use at the catheter vascular access site reduces the incidence of BSIs [12,13,16]. Appropriate use of this antiseptic may also help reduce BSIs in catheterized patients.…”
Section: Discussionsupporting
confidence: 57%
“…Only one high-powered European randomised controlled trial [26] evaluated the efficacy of skin disinfection modalities, i.e., four-step disinfection with scrubbing of the skin (detergent, rinsing, drying and disinfection) versus one-step disinfection (only one application of disinfectant on macroscopically clean skin), with two different antiseptics, povidone-iodine/alcohol versus chlorhexidine-alcohol. Cleaning the skin with detergent is one of the French recommendations devised to reduce the number of microorganisms on the skin and improve the efficacy of disinfection [28,29]. Regardless of the antiseptic used, this study showed that this cleansing step in no way decreased the infection, bacteraemia or catheter colonisation rates.…”
Section: Grade 1+ Strong Consensusmentioning
confidence: 71%
“…The same guidelines recommend the use of CHG- impregnated dressings. 9 CHG suppresses bacterial growth at injection sites and reduces the incidence of CRBSIs. The antimicrobial activity of the CHG dressing is unique among existing dressings.…”
Section: Discussionmentioning
confidence: 99%